New sublittoral species of Laonice (Annelida: Spionidae) from Southern Asian coasts - Sikorski, Andrey (2023)
Four new species of Laonice (Annelida: Spionidae) are described from the southern and southeastern coasts of Asia: L. (Laonice) persica sp. nov., L. (Laonice) siamica sp. nov., L. (Sarsiana) apicelamella sp. nov. and L. (Sarsiana) andamanica sp. nov. Materials were collected within the scope of different environmental surveys performed by the consulting company Creocean, ranging from the Persian Gulf (Indian Ocean) on the west, to the Gulf of Siam (Pacific Ocean) on the east. In addition, specimens found in the Gulf of Siam are tentatively attributed to L. (Sarsiana) sinica, and an English translation of the species description is provided for the first time. Different species subgroups within L. (Sarsiana) are also recognized based on key morphologic characters, though their phylogenetic relevance requires further confirmation. The scientific value of biological material collected during environmental surveys is emphasized, and contractors are encouraged to deposit reference collections in public natural history collections.